A novel workflow to fabricate a patient-specific 3D printed accommodative foot orthosis with personalized latticed metamaterial. (June 2022) - Hudak, Yuri F; Li, Jing-Sheng; Cullum, Scott; Strzelecki, Brian M; Richburg, Chris; Kaufman, G Eli; Abrahamson, Daniel; Heckman, Jeffrey T.; Ripley, Beth; Telfer, Scott; Ledoux, William R; Muir, Brittney C; et al.
Highlights: A metamaterial design allows patient-specific insole stiffness. A novel workflow to fabricate custom 3D printed elastomeric insoles was presented. 3D printed insoles matched or improved durability and a reduced shear stiffness. 3D printed insoles reduced regional plantar pressure compared to standard insoles. Abstract: Patients with diabetes mellitus are at elevated risk for secondary complications that result in lower extremity amputations. Standard of care to prevent these complications involves prescribing custom accommodative insoles that use inefficient and outdated fabrication processes including milling and hand carving. A new thrust of custom 3D printed insoles has shown promise in producing corrective insoles but has not explored accommodative diabetic insoles. Our novel contribution is a metamaterial design application that allows the insole stiffness to vary regionally following patient-specific plantar pressure measurements. We presented a novel workflow to fabricate custom 3D printed elastomeric insoles, a testing method to evaluate the durability, shear stiffness, and compressive stiffness of insole material samples, and a case study to demonstrate how the novel 3D printed insoles performed clinically. Our 3D printed insoles results showed a matched or improved durability, a reduced shear stiffness, and a reduction in plantar pressure in clinical case study compared to standard of care insoles.